Twilight - Preethu P (The Grove, 2015)
'Twilight' is a  poem about the identity crisis faced by an average Indian woman. Religious tradition speaks of her as Shakti ( goddess) who is the primordial cosmic energy representing the divine feminine. At the same time, she has to suffer a lot of atrocities in the patriarchal society, ranging from female infanticide to death. Juniper symbolises the journey in which selfhood is not compromised. In dreams of a glorious past, she chants the Sakti mantra (hymn) and invokes the goddess in the highest tip of the tree of selfhood while the cruel reality binds her to the roots.